Laccase Inhibiting Activity of Some Coumarin Derivatives - Tisma, Marina; Molnar, Maja; Skarica, Marija; Cacic, Milan; Zelic, Bruno (Letters in Organic Chemistry, 2014)
Seven coumarin derivatives were screened for their inhibitory effect on laccase utilizing ABTS and L-DOPA as substrates. 2-[(4-Methyl-2-oxo-2H-1-benzopyran-7-yl)oxy]acetic acid (E)-2-[(dihydroxyphenyl)methylene]hydrazides were proven to be stronger inhibitors than corresponding thiosemicarbazides when ABTS [2,2'-azinobis(3- ethylbenzothiazoline-6-sulfonic acid)] was used as a substrate. In kinetic experiments mixed type inhibition was determined for 2-[(4-methyl-2-oxo-2H-1-benzopyran-7-yl)oxy]acetic acid (E)-2-[(2,5-dihydroxyphenyl)methylene]hydrazide and (E)-2-[(3,4-dihydroxyphenyl)methylene]hydrazide. In reaction of L-DOPA (L-3,4-dihydroxyphenylalanine) oxidation catalyzed by laccase none of the tested compounds has shown inhibitory effect.
Keywords: L-DOPA